Cyclic deformation behavior of a damage tolerant CrMnNi TRIP steel produced by electron beam melting. (September 2018) - Droste, M.; Günther, J.; Kotzem, D.; Walther, F.; Niendorf, T.; Biermann, H.
Highlights: Remarkable hardening capacity and high ductility yield outstanding damage tolerance. EBM states exhibit similar mechanical properties as conventionally processed material. Fine-grained as-build microstructure with an average grain size of 32 μm. Formation of fatigue-induced α′-martensite via intermediate ε-martensite. Properties reveal excellent ability of this steel alloy for AM technologies like EBM. Abstract: A high alloy CrMnNi TRIP steel has been processed by electron beam melting, a powder-bed based additive manufacturing (AM) technology, to investigate its fatigue properties. The material was characterized by average grain sizes of 32 μm in the as-built and 106 μm in the solution annealed state. Total strain controlled fatigue tests with strain amplitudes in the range of 0.25% ≤ Δεt /2 ≤ 1.2% were performed revealing a similar cyclic deformation behavior and α′-martensite evolution compared to a hot pressed reference material. Moreover, the fatigue lives of the EBM states were surprisingly high in consideration of severe process-induced lack of fusion defects of more than 500 μm revealed by investigations of the fracture surfaces. Thus, the impact of these inhomogeneities was substantially alleviated by the outstanding damage tolerance of the present TRIP steel induced by its high ductility and remarkable hardening capacity.